2019
DOI: 10.3892/mmr.2019.10851
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcineurin/NFATc4 signaling attenuates ventilator‑induced lung injury

Abstract: Ventilator-induced lung injury (Vili) is a life-threatening condition caused by the inappropriate use of mechanical ventilation (MV). However, the precise molecular mechanism inducing the development of Vili remains to be elucidated. in the present study, it was revealed that the calcineurin/nFaTc4 signaling pathway mediates the expression of adhesion molecules and proinflammatory cytokines essential for the development of Vili. The present results revealed that a high tidal volume ventilation (HV) caused lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…6b ; Supplementary Data 7 ). Increased expression of Vcam1 was previously reported in the lungs of mechanically ventilated rats 39 and increased Cd44 levels were associated with protective effects in hyperoxia-exposed mice 40 . Signals received by Myofib.…”
Section: Resultsmentioning
confidence: 57%
“…6b ; Supplementary Data 7 ). Increased expression of Vcam1 was previously reported in the lungs of mechanically ventilated rats 39 and increased Cd44 levels were associated with protective effects in hyperoxia-exposed mice 40 . Signals received by Myofib.…”
Section: Resultsmentioning
confidence: 57%
“…Our previous investigation showed that PERK phosphorylation increased the enzymatic activity of its down-stream effecter CaN by direct contact [12]. Activated CaN facilitates the nuclear translocation of NFATc4, which further modulates the transcription of targeted genes including Fas/FasL, COX2 and pro-inflammatory cytokines [15,16,30]. Our in vivo and in vitro studies data showed that PERK silencing inhibited PERK phosphorylation, leading to down-regulation of CaN activity and attenuation of NFATc4 nuclear translocation in CEMCs.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, we also proved that calcineurin (CaN) was a direct downstream effecter of PERK signaling, which facilitated activation of nuclear factor of activated T-cells (NFAT) [12,13]. The activation of PERK/CaN/NFAT pathway was reported to induce cell apoptosis through Fas/FasL pathway and to initiate transcriptions of targeted genes such as interleukins (IL), tumor necrosis factors (TNF) and thromboxanes (TXA) [14][15][16].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…NFATc4-induced inflammation response in different cell types, leading to increases in inflammatory factors and cytokines, which also leads to activations of PDK and Akt sequentially. 18,[23][24][25] In H9C2 cells, overexpression of NFATc4 promoted phosphorylation of PDK1 (Fig. 8A), whereas reduction was observed with the knockdown of NFATc4 (Fig.…”
Section: Nfatc4 Altered Phosphorylation and Acetylation Of Pgc-1amentioning
confidence: 94%